Extreme lower jaw elongation in a placoderm reflects high disparity and modularity in early vertebrate evolution - Melina Jobbins; Martin Rücklin; Marcelo R. Sánchez Villagra; Hervé Lelièvre; Eileen Grogan; Piotr Szrek; Christian Klug (Royal Society Open Science, 2024)
Jaws are a key vertebrate feature that arose early in our evolution. Placoderms are among the first jawed vertebrates; their fossils yield essential knowledge about the early diversification of gnathostome feeding strategies, diets and modularity. Modularity can be expressed through disproportional lengths of lower and upper jaws as in swordfish or halfbeaks. Alienacanthus malkowskii is an arthrodire from the Famennian of Morocco and Poland, whose most remarkable feature is its lower jaw, which is twice as long as the skull. This is the oldest record of such extreme jaw elongation and modularity in vertebrates. The gnathal plates of Alienacanthus possess sharp, posteriorly recurved teeth that continue anterior of the occlusion in the inferognathals. The dentition suggests a catching and trapping live prey function, and the jaw occlusion is unique among placoderms. This armoured ‘fish’ expands the morphological and ecological diversity during one of the first radiations of jawed vertebrates with a combination of features so far unrecorded for arthrodires.